Komunikasi Orangtua-Anak dalam Pengambilan Keputusan Pendidikan - Rini, Yohana Susetyo (Interaksi: Jurnal Ilmu Komunikasi, 2014)
When reaching adolescence, education becomes an important where the existence of major selection in high or vocational school requires the children to choose majors tailored by their interests and talents. On theother hand, parents, with their strategic position in the family, can determine a one-sided decision for their children. This implies the absence of effective communication in the process of decision-making of major selection. The purpose of this study is to describe a dialogue experienced by parents and their child in making decisions of major selection. This qualitative descriptive method makes used of the constructivist paradigmwith phenomenological approach tried to describe the experience of the in-depth communication between parent and children in making the decision to choose a major in their school.The result indicated that both parent and the children were involved in the making of choice. The closer relationship with their parents and an open dialogue also promoted them to understand each other’s desires and expectations were so that the decision was based on mutual understanding. Parents’ roles were limited to directing and giving out considerations and advices. Friends of the same age too could function as ones to share with and provide alternative choices for the children.